2016
DOI: 10.1063/1.4960505
|View full text |Cite
|
Sign up to set email alerts
|

Finite state projection based bounds to compare chemical master equation models using single-cell data

Abstract: Emerging techniques now allow for precise quantification of distributions of biological molecules in single cells. These rapidly advancing experimental methods have created a need for more rigorous and efficient modeling tools. Here, we derive new bounds on the likelihood that observations of single-cell, single-molecule responses come from a discrete stochastic model, posed in the form of the chemical master equation. These strict upper and lower bounds are based on a finite state projection approach, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…78 For example, the reduced models considered here achieved levels of accuracy (i.e., relative errors of 10 −5 or less) that are much higher than one would expect to be necessary to compare models in light of far less accurate data. In light of this finding and the fact that parameter discrimination can be achieved at different levels of accuracy for different combinations of models and data, 79 we suspect that it could be advantageous to build less accurate models that can be evaluated in less time.…”
Section: Discussionmentioning
confidence: 99%
“…78 For example, the reduced models considered here achieved levels of accuracy (i.e., relative errors of 10 −5 or less) that are much higher than one would expect to be necessary to compare models in light of far less accurate data. In light of this finding and the fact that parameter discrimination can be achieved at different levels of accuracy for different combinations of models and data, 79 we suspect that it could be advantageous to build less accurate models that can be evaluated in less time.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology requires solving only a sparse system of ODEs, which can be considerably more efficient than performing large numbers of coupled simulations. Moreover, the method directly provides the precise probability distributions of cell responses, which can be used directly to compute the likelihood that observed experimental heterogeneity data is from a proposed combination of model and parameters [25, 28, 29]. For these reasons, it is expected that the pFSP will become a valuable tool to fit and predict experimentally measured single-cell heterogeneity in fluctuating population sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The particular advantage of the FSP approach is that it can directly and systematically compare stochastic biochemical models to the type of single-cell data that is readily measured using flow cytometry or fluorescence microscopy [25], and as a result the FSP has seen substantial success in the fitting and predicting of single-cell molecular distributions in bacterial [26, 27], yeast [28], and human [29] cells. However, in each of these cases, the population size has been assumed to be constant, and little attention has been given to adapt the FSP approach to explore the coupling of population growth and discrete stochastic molecular dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…Because the CME has no exact solution for most models, we employ the finite state projection (FSP) method to approximate the CME solution and to estimate the full joint probability distributions for gene switching behavior and transcript accumulation [20]. Several recent reviews of the FSP approach and its applications can be found at [14,21,22,23]. A key advantage of the CME and FSP formulation is that they provide systematic approaches to compute and compare the likelihood of data arising from multiple models [1,10,21].…”
Section: A Standard Computational Toolbox For Quantitative Biologymentioning
confidence: 99%
“…Several recent reviews of the FSP approach and its applications can be found at [14,21,22,23]. A key advantage of the CME and FSP formulation is that they provide systematic approaches to compute and compare the likelihood of data arising from multiple models [1,10,21]. With this in mind, we use the Metropolis-Hastings algorithm in conjunction with the FSP analysis to attain more precise constraints on the parameters when fit to simulated data [11].…”
Section: A Standard Computational Toolbox For Quantitative Biologymentioning
confidence: 99%